2000
DOI: 10.1063/1.480989
|View full text |Cite
|
Sign up to set email alerts
|

Interaction second virial coefficients from a recent H2–CO potential energy surface

Abstract: Interaction second virial coefficients for mixtures of hydrogen and CO are computed from a recent rigid rotor potential energy surface [J. Chem. Phys. 108, 3554 (1998)]. The calculations include the most important quantum corrections. A comparison with experimental data indicates that the attractive well of the ab initio surface is too deep by 4%–9%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…Here, we can observe that the JS05 surface agree very well with the CCSD(T)-R12 results while the JS98 surface overestimates the depth of the CO−H 2 potential well by about 10−20 %, as anticipated by Gottfried & McBane (2001). However, the JS05 surface lies slightly below the CCSD(T)-R12 one.…”
Section: Potential Energy Surfacesupporting
confidence: 80%
See 1 more Smart Citation
“…Here, we can observe that the JS05 surface agree very well with the CCSD(T)-R12 results while the JS98 surface overestimates the depth of the CO−H 2 potential well by about 10−20 %, as anticipated by Gottfried & McBane (2001). However, the JS05 surface lies slightly below the CCSD(T)-R12 one.…”
Section: Potential Energy Surfacesupporting
confidence: 80%
“…The JS98 surface has been checked against experiment by a couple of authors. Gottfried & McBane (2001), in particular, computed second virial coefficients below 300 K and showed that the attractive well of the PES was slightly too deep. A modification which consists of multiplying the PES by a factor of 0.93 was therefore suggested by these authors.…”
Section: Introductionmentioning
confidence: 99%
“…Antonova et al (2000) adopted V 98 in their calculations of state-to-state cross sections for CO rotational excitation at collision energies between 795 and 991 cm −1 which were found to be in good agreement with their measurements. The V 98 PES was also utilized in second virial coefficient calculations for mixtures of hydrogen and CO (Gottfried & McBane 2000). A comparison with experimental data suggested that the van der Waals well of the V 98 PES is too deep by 4%-9%, though it represents an improvement over earlier surfaces.…”
Section: The Potential Energy Surfacementioning
confidence: 99%
“…We had originally planned to use this potential to calculate the inelastic cross sections of astrophysical interest as well. However, a study of second virial coefficients calculated from this potential [9] has shown that the attractive well of this ab initio potential-energy surface is too deep. A modification was, therefore, suggested by these authors; that is, multiplication by a factor of 0.93 for the purpose of virial coefficient calculation.…”
Section: Quantum Scattering Calculationsmentioning
confidence: 99%